2017
DOI: 10.1038/tp.2016.258
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for the presence of genetic variants predisposing to psychotic disorders on the non-deleted 22q11.2 allele of VCFS patients

Abstract: The velo-cardio-facial syndrome (VCFS) is caused by hemizygous deletions on chromosome 22q11.2. The VCFS phenotype is complex and characterized by frequent occurrence of neuropsychiatric symptoms with up to 25–30% of cases suffering from psychotic disorders compared with only ~1% in the general population (odds ratio≈20–25). This makes the 22q11.2 deletion one of the most prominent risk factors for schizophrenia. However, its penetrance for neuropsychiatric phenotypes is incomplete suggesting that additional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This could be driven by other genetic risk factors; however, there is no evidence of the presence of genetic factors on the non-deleted 22q11.2 copy to predispose these individuals to the development of, for example, psychotic disorders. 24 , 25 , 26 This suggests that alternative factors, such as environmental and epigenetic factors, could contribute to the development, onset and/or progression of psychiatric phenotypes in 22q11.2DS individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This could be driven by other genetic risk factors; however, there is no evidence of the presence of genetic factors on the non-deleted 22q11.2 copy to predispose these individuals to the development of, for example, psychotic disorders. 24 , 25 , 26 This suggests that alternative factors, such as environmental and epigenetic factors, could contribute to the development, onset and/or progression of psychiatric phenotypes in 22q11.2DS individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The CLTCL1 has a role in synaptic plasticity (KEGG:hsa04721), neural crest development 44 , neuronal depolarization 45 , and histone modification 46 . Two previous case–control studies reported that variants on the 22q11.2 intact chromosome are not major contributors to SZ 36 and psychosis 47 . The haplotype analysis of large multiplex families, in contrast to case–control studies, enables to examine contribution of the 22q11.2 gene variants, inherited together as a haplotype, to psychosis using internal control for comparison that eliminates the need for population stratification.…”
Section: Discussionmentioning
confidence: 87%
“…The etiology of the incomplete penetrance of psychosis in 22q11.2DS is a highly critical question. Regarding genetic explanations, several hypotheses have been raised, ranging from additional genomic mutation outside of the 22q region (Balan et al, 2014; Bassett et al, 2017; Toyosima et al, 2011) to epigenetic factors (Cirillo et al, 2014; Singh et al, 2002; Starnawska et al, 2017), without forgetting the potential role of the other allele and especially COMT polymorphisms (Gothelf et al, 2007, Gothelf et al, 2014; Guipponi et al, 2017; Merico et al, 2015; Thompson et al, 2017) or intergenic noncoding RNA genes (Merico et al, 2015). A more integrative model suggests that psychotic symptoms may occur from genetic risk combined with negative life events, traumatic experiences, and/or attachment disorder (Biswas and Furniss, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, behavioural measures can be contaminated by response-related unspecific processes such as decision-making or response inhibition (Azuma et al, 2015; Leleu et al, 2016). Second, classical group studies insufficiently control genetic or environmental stress variability that could mediate the incomplete penetrance for psychiatric phenotypes (Biswas and Furniss, 2016; Chung et al, 2015; Guipponi et al, 2017; Toyosima et al, 2011). It remains thus unclear whether neurocognitive markers identified in group studies can be used in clinical care, i.e., for individual participants.…”
Section: Introductionmentioning
confidence: 99%